GESTÃO DA EDUCAÇÃO A DISTÂNCIA: SISTEMA E ESTRUTURA ORGANIZACIONAL DIANTE DO ENADE - Antonio Roberto Coelho Serra (Revista Gestão Universitária na América Latina, 2012)
This paper focuses on the various conceptions and theoretical foundations about the approaches on systems of distance education and organizational structure, for design of so called configuration of the management of distance education (EAD). It examined the relation between the configurations of managements of distance courses in administration, pilot project of the UAB (Open University of Brazil) and their concepts defined by National Examination Performance of Students (Enade). The work starts from a description of the organizational structure of the area responsible for distance education in the surveyed universities. Also were analyzed and compared the DE systems of the pilot course of UAB, based on the benchmarks of MEC (Department of Education) for quality for higher distance education. It is a research predominantly qualitative, descriptive, explanatory and multi-case, whose data collection was made from interviews, focus groups, questionnaires and online documents. It became clear the strong and direct relationship between the configurations of managements of the pilot course and their results in the ENADE. So, it is recognized that the differences in the results in the Enade by the investigated education institutions, has direct relation with the way their sectors responsible for intermediation of ED are structured.